MANAJEMEN PEMBELAJARAN BERBASIS NILAI KEARIFAN LOKAL SUNDA HADE TATA HADE BASA DALAM INTERNALISASI KARAKTER SISWA SEKOLAH - Ramdani, Pajar; Tatang Suryana; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze in-depth the management of learning based on the Sundanese local wisdom value of hade tata hade basa in the process of internalizing elementary school students' character. The urgency of this research is based on the phenomenon of student character degradation as an implication of globalization and digital technology, as well as the suboptimal integration of local cultural values ​​into learning practices. This study used a qualitative approach with descriptive methods. The research subjects included principals, teachers, and students at SDN 2 Babakancikao and SDN 1 Mulyamekar in Purwakarta Regency. Data collection was conducted through participatory observation, in-depth interviews, and documentation studies, while data analysis referred to the interactive model of Miles and Huberman. The results indicate that the management of learning based on the value of hade tata hade basa has not been implemented optimally and systematically. At the planning stage, the integration of local wisdom values ​​has not been explicitly formulated in the learning materials. At the implementation stage, internalization of values ​​is carried out through habituation practices, but is not supported by structured pedagogical strategies. Meanwhile, at the evaluation stage, assessments are still oriented towards cognitive aspects and do not specifically accommodate character indicators. Supporting factors include a conducive school culture and leadership support, while inhibiting factors include limited teacher competency and a lack of implementation guidance. These findings underscore the need to strengthen integrated learning management based on local cultural values ​​to continuously improve the effectiveness of student character internalization.